Method for producing nickel foil through electrolytic method

By using precious metal plates and titanium plates to perform electrolytic deposition in the electrolyte, the problem of difficult to obtain flat and smooth thin nickel foils in the prior art is solved, and efficient production of ultra-thin nickel foils with a thickness of less than 5 μm is achieved, with good mechanical properties and environmental friendly characteristics.

CN119640348AActive Publication Date: 2025-03-18CHINA ENFI ENG CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510111580.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-03-18
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

It is difficult to obtain flat and smooth thin nickel foils, especially ultra-thin nickel foils with thicknesses less than 5 μm.

Method used

Nickel foil is prepared by electrolytic deposition by controlling the electrolytic temperature, pH value and current density by controlling the electrolytic temperature, pH value and current density.

Benefits of technology

It realizes the production of ultra-thin nickel foil with flat and smooth surface, with a thickness less than 5μm, low roughness, good mechanical properties, and avoids anode sludge pollution and chloride ion corrosion. It has simple process and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640348A_ABST
    Figure CN119640348A_ABST
Patent Text Reader

Abstract

The invention provides a method for producing a nickel foil by an electrolytic process, which comprises the following steps: by taking a noble metal plate as an anode and a titanium plate as a cathode, putting the anode and the cathode in an electrolyte, electrifying direct current for electrolysis, electrically depositing a nickel metal layer on the titanium plate, and stripping the nickel metal layer to obtain the nickel foil, the electrolyte comprises water and the following components by concentration: 300-600g / L of nickel sulfate; 10-40 g / L of a pH buffer agent; 0.05-2 g / L of a brightener; the pH value of the electrolyte is 1-5, and in the electrolysis process, the electrolysis temperature is 50-75 DEG C, and the current density is 20-80 A / dm < 2 >. Based on the method for producing the nickel foil through the electrolytic method, the non-porous nickel foil with the bright surface, low roughness and low thickness is obtained, and the problem that in the prior art, flat and smooth thin nickel foil cannot be obtained is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical deposition, in particular to a method for producing nickel foil by electrolysis. Background Art

[0002] Nickel foil is a raw material used in electronics, telecommunications, instrumentation and other industries. In recent years, the demand for thin nickel foil has been increasing day by day, and its application range has become wider and wider. At present, there are two main methods for making nickel foil: rolling method and electrolytic method (electroforming method). The formation process of nickel foil produced by rolling method is from thick to thin. To produce thin nickel foil, it needs to be rolled repeatedly many times. The production process is long and the cost is high. It is difficult to obtain thinner nickel foil and the thickness is uneven. The width of nickel foil is also limited. The formation process of nickel foil produced by electrolytic method is from thin to thick, but it is formed by electroplating once, with high yield and low processing cost. It is especially suitable for the production of wide and thin nickel foil. Generally, electrolytic nickel plate or scraps of electrolytic nickel are used as anodes for electroplating. Nickel chloride needs to be added as anode activator, which will corrode the equipment and is not conducive to the long-term operation of the equipment. In addition, the anode plate needs to be obtained by electroplating, which increases the production process and increases the cost. CN103031578A discloses an electrolytic method for producing nickel foil, wherein a lead-silver plate or a titanium plate is used as an anode and an electrolyte composed of sulfuric acid and boric acid is used to prepare the nickel foil, thereby obtaining a nickel foil having a smooth appearance, but the obtained nickel foil is relatively thick. Therefore, it is of great significance to develop a flat and smooth thin nickel foil. Summary of the invention

[0003] The main purpose of the present invention is to provide a method for producing nickel foil by electrolysis to solve the problem that a flat, smooth and thin nickel foil cannot be obtained in the prior art.

[0004] In order to achieve the above object, the present invention provides a method for producing nickel foil by electrolysis, wherein a noble metal plate is used as an anode and a titanium plate is used as a cathode, the anode and the cathode are both placed in an electrolyte, direct current is passed for electrolysis, and nickel foil is prepared by electrodeposition on the titanium plate;

[0005] The electrolyte contains water and the following components in the following concentrations:

[0006] Nickel sulfate 300~600g / L;

[0007] pH buffer 10-40 g / L;

[0008] Brightener 0.05~2g / L;

[0009] Wetting agent 0.005~0.2g / L;

[0010] The pH of the electrolyte is 1-5. During the electrolysis process, the electrolysis temperature is 50-75°C and the current density is 20-80A / dm 2 .

[0011] Furthermore, the noble metal anode plate is selected from one of platinum-rhodium, rhodium-iridium, and platinum-rhodium-iridium noble metal plates.

[0012] Furthermore, the wetting agent is selected from one or more of sodium dodecyl sulfate, sodium 2-ethylhexyl sulfate, sodium dihexyl sulfosuccinate, and sodium dipentyl sulfosuccinate.

[0013] Preferably, the wetting agent is selected from one of dihexyl sodium sulfosuccinate or dipentyl sodium sulfosuccinate or a mixture of the two.

[0014] Preferably, the concentration of the wetting agent is 0.05-0.1 g / L.

[0015] Furthermore, the brightener is one or more selected from saccharin, 4-hydroxy-2-butynyl-2-hydroxyalkyl ether, 1,4-butynediol, 2-propynyl-2-hydroxyalkyl ether, sodium allyl sulfonate, propargyl alcohol, glycerol monopropynyl ether, sulfopropynyl ether sodium salt and carbonyl compound sulfonate sodium salt.

[0016] Preferably, the concentration of the brightener is 0.2-2 g / L.

[0017] Furthermore, the pH buffer is selected from boric acid, sodium citrate or a mixture of the two.

[0018] Preferably, the concentration of the pH buffer is 30-40 g / L.

[0019] Furthermore, the concentration of nickel sulfate is 320-400 g / L.

[0020] Furthermore, the pH of the electrolyte is 2.5 to 4.5, the electrolysis temperature is 55 to 65°C, and the current density is 30 to 40 A / dm 2 .

[0021] Furthermore, the distance between the anode and the cathode is 5 to 20 mm.

[0022] Preferably, the distance between the two poles is 10-20 mm.

[0023] Furthermore, the electrolysis time is 10 to 60 seconds.

[0024] Preferably, the electrolysis time is 20 to 30 seconds.

[0025] Furthermore, the titanium plate after electrodeposition is taken out from the electrolyte, and then washed and dried in sequence, and then the nickel metal layer formed after deposition is peeled off to obtain nickel foil.

[0026] By applying the technical solution of the present invention, a precious metal plate is used as an anode and a titanium plate is used as a cathode, and by controlling the ratio of additives such as a wetting agent, a buffer, a brightener, and the like and the electrolysis conditions, nickel ions can be uniformly precipitated on the entire cathode plate, thereby obtaining a non-porous nickel foil with low roughness and low thickness; in addition, the precious metal plate is used to replace the nickel plate as the anode, thereby avoiding the pollution of the system caused by the anode mud generated by the anode, and the nickel sulfate in the solution is directly electrolyzed without adding nickel chloride, thereby avoiding the influence of chloride ions on the electrolysis system, and the process is simple and the cost is low.

[0027] By adopting the method for producing nickel foil by electrolysis of the present invention, an ultra-thin (thickness less than 5 μm) nickel foil with a flat and smooth surface can be obtained, and the production method is friendly to equipment and the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0029] Figure 1 The surface morphology of the nickel foil prepared in Example 1 of the present invention is shown;

[0030] Figure 2 The surface morphology of the nickel metal layer after electrolysis in Comparative Example 2 of the present invention is shown;

[0031] Figure 3 The surface morphology of the nickel foil prepared in Comparative Example 4 of the present invention is shown;

[0032] Figure 4 The surface morphology of the nickel foil prepared in Comparative Example 5 of the present invention is shown;

[0033] Figure 5 The surface morphology of the nickel foil prepared in Comparative Example 6 of the present invention is shown. DETAILED DESCRIPTION

[0034] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0035] As described in the background technology, there is a problem in the prior art that it is impossible to obtain a flat and smooth thin nickel foil, especially an ultra-thin nickel foil with a thickness of less than 5 μm. In order to solve the above problem, according to one aspect of the present invention, a method for producing nickel foil by electrolysis is provided, wherein a precious metal plate is used as an anode and a titanium plate is used as a cathode. The anode and the cathode are both placed in an electrolyte, and direct current is passed for electrolysis to prepare nickel foil by electrodeposition on the titanium plate; the electrolyte contains water and the following components in the following concentrations: nickel sulfate 300-600 g / L; pH buffer 10-40 g / L; brightener 0.05-2 g / L; wetting agent 0.005-0.2 g / L; the pH of the electrolyte is 1-5, and during the electrolysis process, the electrolysis temperature is 50-75°C, and the current density is 20-80 A / dm 2 .

[0036] In order to obtain a nonporous nickel foil with low roughness and small thickness, the present invention provides a method for producing nickel foil by electrolysis, using a precious metal plate as an anode and a titanium plate as a cathode, and by controlling the ratio of additives such as a wetting agent, a buffer, a brightener, and the like and the electrolysis conditions, nickel ions can be uniformly precipitated on the entire cathode plate, thereby obtaining a nonporous nickel foil with low roughness and low thickness; in addition, a precious metal plate is used to replace a nickel plate as an anode, thereby avoiding the pollution of the system caused by the anode mud generated by the anode, and the nickel sulfate in the solution is directly electrolyzed without the need to add nickel chloride, thereby avoiding the influence of chloride ions on the electrolysis system, and the process is simple and the cost is low. The method for producing nickel foil by electrolysis of the present invention can obtain an ultra-thin (thickness less than 5 μm) nickel foil with a smooth surface, and the production method is friendly to equipment and the environment.

[0037] In a preferred embodiment, the precious metal anode plate is selected from one of platinum-rhodium, rhodium-iridium, and platinum-rhodium-iridium precious metal plates. The above precious metals have high hardness, good corrosion resistance, and long service life.

[0038] In a preferred embodiment, the wetting agent is selected from one or more of sodium dodecyl sulfate, sodium 2-ethylhexyl sulfate, sodium dihexyl sulfonate, and sodium diamyl sulfonate; preferably, the wetting agent is selected from one or a mixture of sodium dihexyl sulfonate or sodium diamyl sulfonate, which can promote more uniform precipitation of nickel ions on the entire cathode plate and reduce the probability of pinhole generation; in order to reduce costs and obtain high-quality ultra-thin nickel foil, the preferred concentration of the wetting agent is 0.05-0.1 g / L.

[0039] In a preferred embodiment, the brightener is selected from one or more of saccharin, 4-hydroxy-2-butynyl-2-hydroxyalkyl ether, 1,4-butynediol, 2-propynyl-2-hydroxyalkyl ether, sodium allyl sulfonate, propargyl alcohol, glycerol monopropynyl ether, sulfopropynyl ether sodium salt and carbonyl compound sulfonate sodium salt. The above brightener can not only refine the grain size of the coating and brighten the coating, but also better improve the stress distribution state of the coating and reduce the brittleness of the coating; preferably, the concentration of the brightener is 0.2-2 g / L.

[0040] In a preferred embodiment, the pH buffer is selected from boric acid, sodium citrate or a mixture of the two; the preferred concentration of the pH buffer is 30-40 g / L, which can better control the stability and uniformity of the coating of the electrolyte system in the present invention and improve the surface morphology quality of the coating.

[0041] In a preferred embodiment, the concentration of nickel sulfate is 320-400 g / L. Under this condition, a complete ultra-thin nickel foil with a flat and smooth surface can be formed with low production cost.

[0042] When the pH is low, under the same electrolysis conditions, the nickel foil has a small thickness, poor mechanical properties, low electrolysis efficiency, and high energy consumption. When the pH is too high, the nickel foil becomes rougher and the performance deteriorates. When the temperature is low, the nickel foil is not easy to form. When the temperature is too high, the nickel foil becomes rougher. In order to obtain a smoother nickel foil with low thickness and high mechanical properties while reducing energy consumption, in a preferred embodiment, the pH of the electrolyte is 2.5-4.5, the electrolysis temperature is 55-65°C, and the current density is 30-40A / dm 2 .

[0043] In order to obtain a smoother ultra-thin nickel foil and higher production efficiency, in a preferred embodiment, the distance between the anode and the cathode is 5 to 20 mm; preferably, the distance between the anode and the cathode is 10 to 20 mm.

[0044] In a preferred embodiment, the electrolysis time is 10 to 60 seconds; preferably, the electrolysis time is 20 to 30 seconds, so as to obtain a smooth and dense ultra-thin nickel foil.

[0045] In a preferred embodiment, the titanium plate after electrodeposition is taken out from the electrolyte, and then washed and dried in sequence, and then the nickel metal layer formed after deposition is peeled off to obtain nickel foil.

[0046] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0047] Example 1

[0048] A method for producing nickel foil by electrolysis, the specific steps are as follows:

[0049] Platinum-rhodium plate is used as anode and titanium plate is used as cathode. Both anode and cathode are placed in electrolyte and direct current is passed for electrolysis to deposit nickel metal layer on titanium plate. The distance between the two electrodes is 10mm and the current density is 40A / dm 2 The concentrations of the components in the electrolyte (solvent is water) are: NiSO4 350g / L, H3BO3 40g / L, sodium diamyl sulfonate succinate 0.05g / L, saccharin 1g / L, the pH of the electrolyte is 3, the electrolysis temperature is maintained at 60°C in a water bath, and the electrolysis time is 20s. After the electrolysis is completed, the titanium plate after the electrodeposition of the nickel metal layer is taken out of the electrolyte and washed with water. After washing, it is dried and dehydrated. After drying, the nickel metal layer is peeled off to obtain a nickel foil with a bright and flat surface, complete and without pinholes, such as Figure 1 As shown, the nickel foil has a thickness of 4.89 μm, a roughness of Ra0.245 μm, and a tensile strength of 866 N / mm 2 , the elongation is 8.2%.

[0050] Implementation 2

[0051] A method for producing nickel foil by electrolysis, the specific steps are as follows:

[0052] Platinum-rhodium plate is used as anode and titanium plate is used as cathode. Both anode and cathode are placed in electrolyte and direct current is passed for electrolysis to deposit nickel metal layer on titanium plate. The distance between the two electrodes is 20mm and the current density is 40A / dm 2 The concentrations of the components in the electrolyte (the solvent is water) are: NiSO4 350g / L, H3BO3 40g / L, sodium diamyl sulfonate succinate 0.05g / L, saccharin 1g / L, the pH of the electrolyte is 3, the electrolysis temperature is maintained at 60°C in a water bath, and the electrolysis time is 20s. After the electrolysis is completed, the titanium plate after the electrodeposition of the nickel metal layer is taken out of the electrolyte and washed with water. After washing, it is dried and dehydrated. After drying, the nickel metal layer is peeled off to obtain a nickel foil with a bright and flat surface, complete and pinhole-free. The nickel foil has a thickness of 4.96μm, a roughness of Ra0.207μm, and a tensile strength of 846N / mm 2 , the elongation is 8.4%.

[0053] Implementation 3

[0054] A method for producing nickel foil by electrolysis, the specific steps are as follows:

[0055] Platinum-rhodium plate is used as anode and titanium plate is used as cathode. Both anode and cathode are placed in electrolyte and direct current is passed for electrolysis to deposit nickel metal layer on titanium plate. The distance between the two electrodes is 10mm and the current density is 30A / dm 2The concentrations of the components in the electrolyte (the solvent is water) are: NiSO4 350g / L, H3BO3 40g / L, sodium diamyl sulfonate succinate 0.05g / L, saccharin 1g / L, the pH value of the electrolyte is 3, the electrolysis temperature is maintained at 60°C in a water bath, and the electrolysis time is 20s. After the electrolysis is completed, the titanium plate after the electrodeposition of the nickel metal layer is taken out of the electrolyte and washed with water. After washing, it is dried and dehydrated. After drying, the nickel metal layer is peeled off to obtain a nickel foil with a bright, flat, complete and pinhole-free surface. The thickness of the nickel foil is 3.58μm, the roughness is Ra0.292μm, and the tensile strength is 782N / mm 2 , the elongation is 7.6%.

[0056] Implementation 4

[0057] A method for producing nickel foil by electrolysis, the specific steps are as follows:

[0058] Platinum-rhodium plate is used as anode and titanium plate is used as cathode. Both anode and cathode are placed in electrolyte and direct current is passed for electrolysis to deposit nickel metal layer on titanium plate. The distance between the two electrodes is 10mm and the current density is 40A / dm 2 The concentrations of the components in the electrolyte (the solvent is water) are: NiSO4 350g / L, H3BO3 40g / L, sodium diamyl sulfonate succinate 0.1g / L, saccharin 1g / L, the pH of the electrolyte is 3, the electrolysis temperature is maintained at 60°C in a water bath, and the electrolysis time is 20s. After the electrolysis is completed, the titanium plate after the electrodeposition of the nickel metal layer is taken out of the electrolyte and washed with water. After washing, it is dried and dehydrated. After drying, the nickel metal layer is peeled off to obtain a nickel foil with a bright and flat surface, complete and pinhole-free. The nickel metal layer is peeled off to obtain a nickel foil with a thickness of 4.76μm, a roughness of Ra0.179μm, and a tensile strength of 782N / mm 2 , the elongation is 7.6%.

[0059] Implementation 5

[0060] A method for producing nickel foil by electrolysis, the specific steps are as follows:

[0061] Platinum-rhodium plate is used as anode and titanium plate is used as cathode. Both anode and cathode are placed in electrolyte and direct current is passed for electrolysis to deposit nickel metal layer on titanium plate. The distance between the two electrodes is 10mm and the current density is 40A / dm 2The concentrations of the components in the electrolyte (the solvent is water) are: NiSO4 350g / L, H3BO3 40g / L, sodium diamyl sulfonate succinate 0.05g / L, saccharin 2g / L, the pH of the electrolyte is 3, the electrolysis temperature is maintained at 60°C in a water bath, and the electrolysis time is 20s. After the electrolysis is completed, the titanium plate after the electrodeposition of the nickel metal layer is taken out of the electrolyte and washed with water. After washing, it is dried and dehydrated. After drying, the nickel metal layer is peeled off to obtain a nickel foil with a bright, flat, complete and pinhole-free surface. The thickness of the nickel foil is 4.56μm, the roughness is Ra0.198μm, and the tensile strength is 846N / mm 2 , the elongation is 8.9%.

[0062] Implementation List 6

[0063] A method for producing nickel foil by electrolysis, the specific steps are as follows:

[0064] Platinum-rhodium plate is used as anode and titanium plate is used as cathode. Both anode and cathode are placed in electrolyte and direct current is passed for electrolysis to deposit nickel metal layer on titanium plate. The distance between the two electrodes is 10mm and the current density is 40A / dm 2 The concentrations of the components in the electrolyte (the solvent is water) are: NiSO4 400g / L, H3BO3 30g / L, sodium diamyl sulfonate succinate 0.05g / L, saccharin 1g / L, the pH of the electrolyte is 3, the electrolysis temperature is maintained at 60°C in a water bath, and the electrolysis time is 20s. After the electrolysis is completed, the titanium plate after the electrodeposition of the nickel metal layer is taken out of the electrolyte and washed with water. After washing, it is dried and dehydrated. After drying, the nickel metal layer is peeled off to obtain a nickel foil with a bright, flat, complete and pinhole-free surface. The thickness of the nickel foil is 4.81μm, the roughness is Ra0.249μm, and the tensile strength is 782N / mm 2 , the elongation is 7.6%.

[0065] Example 7

[0066] A method for producing nickel foil by electrolysis, the specific steps are as follows:

[0067] Platinum-rhodium plate is used as anode and titanium plate is used as cathode. Both anode and cathode are placed in electrolyte and direct current is passed for electrolysis to deposit nickel metal layer on titanium plate. The distance between the two electrodes is 5mm and the current density is 20A / dm 2The concentrations of the components in the electrolyte (the solvent is water) are: NiSO4 300g / L, H3BO3 10g / L, sodium diamyl sulfonate succinate 0.005g / L, 4-hydroxy-2-butynyl-2-hydroxyalkyl ether 0.05g / L, the pH of the electrolyte is 2, the electrolysis temperature is maintained at 50°C in a water bath, and the electrolysis time is 20s. After the electrolysis is completed, the titanium plate after the electrodeposition of the nickel metal layer is taken out of the electrolyte and washed with water. After washing, it is dried and dehydrated. After drying, the nickel metal layer is peeled off to obtain a nickel foil with a bright, flat, complete and pinhole-free surface. The nickel metal layer is peeled off to obtain a nickel foil with a thickness of 2.91μm, a roughness of Ra0.379μm, and a tensile strength of 613N / mm 2 , the elongation is 6.9%.

[0068] Example 8

[0069] A method for producing nickel foil by electrolysis, the specific steps are as follows:

[0070] Platinum-rhodium plate is used as anode and titanium plate is used as cathode. Both anode and cathode are placed in electrolyte and direct current is passed for electrolysis to deposit nickel metal layer on titanium plate. The distance between the two electrodes is 10mm and the current density is 80A / dm 2 The concentrations of the components in the electrolyte (the solvent is water) are: NiSO4 600g / L, H3BO3 40g / L, sodium diamyl sulfonate succinate 0.1g / L, 1,4-butynediol 2g / L, the pH of the electrolyte is 5, the electrolysis temperature is maintained at 75°C in a water bath, and the electrolysis time is 60s. After the electrolysis is completed, the titanium plate after the electrodeposition of the nickel metal layer is taken out of the electrolyte and washed with water. After washing, it is dried and dehydrated. After drying, the nickel metal layer is peeled off to obtain a nickel foil with a bright, flat, complete and pinhole-free surface. The nickel metal layer is peeled off to obtain a nickel foil with a thickness of 4.85μm, a roughness of Ra0.335μm, and a tensile strength of 816N / mm 2 , the elongation is 7.9%.

[0071] Example 9

[0072] The only difference from Example 1 is that the wetting agent sodium dihexyl sulfosuccinate is replaced by sodium dodecyl sulfate. The nickel foil obtained has a bright, smooth, complete and pinhole-free surface, a nickel foil thickness of 4.92 μm, a roughness Ra of 0.354 μm, and a tensile strength of 720 N / mm 2 , the elongation is 6.8%.

[0073] Example 10

[0074] The only difference between the embodiment 1 and the embodiment 1 is that the wetting agent sodium dihexyl sulfosuccinate is replaced by sodium dipentyl sulfosuccinate.

[0075] Finally, a nickel foil with a bright, smooth, complete and pinhole-free surface was obtained. The thickness of the nickel foil was 4.37 μm, the roughness Ra was 0.228 μm, and the tensile strength was 898 N / mm. 2 , the elongation is 8%.

[0076] Embodiment 11

[0077] The only difference between the above-mentioned embodiment and the embodiment 1 is that the wetting agent sodium dihexyl sulfosuccinate is replaced by sodium 2-ethylhexyl sulfate.

[0078] Finally, a nickel foil with a bright, smooth, complete and pinhole-free surface was obtained. The thickness of the nickel foil was 4.74 μm, the roughness Ra was 0.396 μm, and the tensile strength was 628 N / mm. 2 , the elongation is 7.2%.

[0079] Example 12

[0080] The only difference from Example 1 is that the nickel sulfate is 500 g / L. The nickel foil finally obtained has a bright and smooth surface, is complete and has no pinholes. The nickel foil has a thickness of 5.08 μm, a roughness Ra of 0.316 μm, and a tensile strength of 827 N / mm 2 , the elongation δ is 7.9%.

[0081] Embodiment 13

[0082] The only difference between it and Example 1 is that the pH is 2.

[0083] The resulting nickel foil has a bright, smooth, complete and pinhole-free surface. The thickness of the nickel foil is 4.21 μm, the roughness Ra is 0.275 μm, and the tensile strength is 632 N / mm. 2 , the elongation is 6.9%.

[0084] Embodiment 14

[0085] The only difference from Example 1 is that the temperature is 75°C.

[0086] Finally, a nickel foil with a bright, smooth, complete and pinhole-free surface was obtained. The thickness of the nickel foil was 4.97 μm, the roughness Ra was 0.361 μm, and the tensile strength was 753 N / mm. 2 , the elongation is 7.9%.

[0087] Embodiment 15

[0088] The difference between the above method and Example 1 is that the concentration of sodium dihexyl sulfosuccinate in the electrolyte during the preparation process is 0.2 g / L.

[0089] Finally, a nickel foil with a bright, smooth, complete and pinhole-free surface was obtained. The thickness of the nickel foil was 4.82 μm, the roughness was Ra0.256 μm, and the tensile strength was 852 N / mm. 2 , the elongation is 8.1%.

[0090] Comparative Example 1

[0091] The difference from Example 1 is that the concentration of H3BO3 in the electrolyte is 2 g / L. The specific preparation steps are as follows:

[0092] Platinum-rhodium plate is used as anode and titanium plate is used as cathode. Both anode and cathode are placed in electrolyte and direct current is passed for electrolysis to deposit nickel metal layer on titanium plate. The distance between the two electrodes is 10mm and the current density is 40A / dm 2 The concentrations of the components in the electrolyte (the solvent is water) are: NiSO4 350g / L, H3BO3 2g / L, sodium diamyl sulfonate succinate 0.05g / L, saccharin 1g / L, the pH of the electrolyte is 3, the electrolysis temperature is maintained at 60°C in a water bath, and the electrolysis time is 20s. After the electrolysis is completed, the titanium plate after the electrodeposition of the nickel metal layer is taken out of the electrolyte and washed with water. After washing, it is dried and dehydrated. After drying, the nickel metal layer is peeled off to obtain nickel foil. The thickness of the nickel foil is 5.02μm, the roughness is Ra0.937μm, and the tensile strength is 637N / mm 2 , the elongation is 6.3%.

[0093] Comparative Example 2

[0094] The difference between the embodiment 1 and the embodiment 1 is that the water bath temperature is 40° C. The specific steps are as follows:

[0095] Platinum-rhodium plate is used as anode and titanium plate is used as cathode. Both anode and cathode are placed in electrolyte and direct current is passed for electrolysis to deposit nickel metal layer on titanium plate. The distance between the two plates is 10mm and the current density is 40A / dm 2 The concentration of each component in the electrolyte (solvent is water) is: NiSO4 350g / L, H3BO3 40g / L, sodium diamyl sulfonate succinate 0.05g / L, saccharin 1g / L, the pH of the electrolyte is 3, the water bath maintains the electrolysis temperature at 40℃, and the electrolysis time is 20s. After the electrolysis is completed, the nickel metal layer peels and breaks, and has no shape, such as Figure 2 shown.

[0096] Comparative Example 3

[0097] The difference from Example 1 is that the concentration of H3BO3 in the electrolyte is 2 g / L, the electrolysis time is 60 s, and the specific steps are as follows:

[0098] Platinum-rhodium plate is used as anode and titanium plate is used as cathode. Both anode and cathode are placed in electrolyte and direct current is passed for electrolysis to deposit nickel metal layer on titanium plate. The distance between the two electrodes is 10mm and the current density is 40A / dm 2 The concentrations of the components in the electrolyte (the solvent is water) are: NiSO4 350g / L, H3BO3 2g / L, sodium diamyl sulfonate succinate 0.05g / L, saccharin 1g / L, the pH of the electrolyte is 3, the electrolysis temperature is maintained at 60°C in a water bath, and the electrolysis time is 60s. After the electrolysis is completed, the titanium plate after the electrodeposition of the nickel metal layer is taken out of the electrolyte and washed with water. After washing, it is dried and dehydrated. After drying, the nickel metal layer is peeled off to obtain nickel foil. The thickness of the nickel foil is 14.96μm, the roughness is Ra0.332μm, and the tensile strength is 795N / mm 2 , the elongation is 7.4%.

[0099] Comparative Example 4

[0100] The difference between this embodiment and Example 1 is that no wetting agent, sodium dihexyl sulfosuccinate, is added to the electrolyte.

[0101] The final nickel foil has a thickness of 4.98 μm, a roughness of Ra0.694 μm, and a tensile strength of 628 N / mm. 2 , the elongation is 7.2%, and tiny pinholes appear in the nickel foil, such as Figure 3 shown.

[0102] Comparative Example 5

[0103] The difference from Example 1 is that the concentration of sodium dihexyl sulfosuccinate in the electrolyte is 0.003 g / L.

[0104] The final nickel foil has a thickness of 4.74μm, a roughness of Ra0.372μm, and a tensile strength of 754N / mm. 2 , the elongation is 7.6%, and a small number of pinholes appear in the nickel foil, such as Figure 4 shown.

[0105] Comparative Example 6

[0106] The only difference between it and Example 1 is that nickel sulfate is 200 g / L. The nickel metal layer after electrolysis is not formed. Figure 5 shown.

[0107] Among them, the roughness of the nickel foil is measured by a roughness meter in accordance with the standard ISO8503, the thickness of the nickel foil is measured by a film thickness tester in accordance with the standard GB / T36053-2018, and the tensile strength and elongation of the nickel foil are tested by a tensile strength tester in accordance with GB / T228.

[0108] It can be seen from the nickel foil thickness data, roughness data, tensile strength and elongation in Examples 1 to 15 and Comparative Examples 1 to 6 that, compared with Comparative Examples 1-6, Examples 1 to 11 prepared nickel foil with low roughness, low thickness and good mechanical properties by controlling the ratio of additives such as wetting agents, buffers, brighteners, and electrolysis conditions such as temperature, pH, and current density. The thickness of the nickel foil (2.91 to 4.96 μm) is less than 5 μm, and the roughness (Ra0.179 to Ra0.396 μm) is less than Ra0.4 μm. In addition, it can be seen from the data in Examples 1 to 15 and Comparative Examples 1 to 6 that the addition of an appropriate amount of buffer and an appropriate amount of wetting agent in the electrolyte system can promote the uniform precipitation of nickel ions on the entire cathode plate, form a dense structure, and reduce the roughness of the nickel foil, especially when sodium dihexyl sulfonate succinate or sodium dipentyl sulfonate succinate is used as a wetting agent (see Example 1, Examples 9-11), the roughness of the nickel foil is significantly reduced; from the comparison of Comparative Examples 4 and 5 with Example 1, it can be seen that when no wetting agent is added or when the amount of the wetting agent sodium dihexyl sulfonate succinate added is too small, pinholes appear in the nickel foil and the surface is incomplete; from the comparison of Comparative Examples 1 and 3 with Example 1, it can be seen that when the amount of the buffer H3BO3 added is too small, in order to obtain a nickel foil with lower roughness, it is necessary to increase the electrolysis time, which results in an excessively large thickness of the nickel foil. Furthermore, when the water bath temperature is too low, the nickel metal layer peels and breaks and does not take shape (see Comparative Example 2). When the nickel sulfate concentration is too low, the nickel metal layer does not take shape after the electrolysis is completed (see Comparative Example 6).

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for producing nickel foil by electrolysis, characterized in that: A noble metal plate is used as an anode and a titanium plate is used as a cathode. The anode and the cathode are placed in an electrolyte, and direct current is passed for electrolysis to prepare nickel foil by electrodeposition on the titanium plate. The electrolyte comprises water and the following components: Nickel sulfate 300~600g / L; pH buffer 10-40 g / L; Brightener 0.05~2g / L; Wetting agent 0.005~0.2g / L; The pH of the electrolyte is 1 to 5. During the electrolysis process, the electrolysis temperature is 50 to 75° C. and the current density is 20 to 80 A / dm 2 .

2. The method for producing nickel foil by electrolysis according to claim 1, characterized in that: The noble metal anode plate is selected from one of platinum-rhodium, rhodium-iridium, and platinum-rhodium-iridium noble metal plates.

3. The method for producing nickel foil by electrolysis according to claim 1, characterized in that: The wetting agent is selected from one or more of sodium dodecyl sulfate, sodium 2-ethylhexyl sulfate, sodium dihexyl sulfosuccinate, and sodium dipentyl sulfosuccinate; Preferably, the wetting agent is selected from one of dihexyl sodium sulfosuccinate or dipentyl sodium sulfosuccinate or a mixture of the two; Preferably, the concentration of the wetting agent is 0.05-0.1 g / L.

4. The method for producing nickel foil by electrolysis according to claim 1, characterized in that: The brightener is one or more selected from saccharin, 4-hydroxy-2-butynyl-2-hydroxyalkyl ether, 1,4-butynediol, 2-propynyl-2-hydroxyalkyl ether, sodium allyl sulfonate, propynyl alcohol, glycerol monopropynyl ether, sulfopropynyl ether sodium salt and carbonyl compound sulfonate sodium salt; Preferably, the concentration of the brightener is 0.2-2 g / L.

5. The method for producing nickel foil by electrolysis according to claim 1, characterized in that: The pH buffer is selected from boric acid, sodium citrate or a mixture of the two; Preferably, the concentration of the pH buffer is 30-40 g / L.

6. The method for producing nickel foil by electrolysis according to claim 1, characterized in that: The concentration of the nickel sulfate is 320-400 g / L.

7. The method for producing nickel foil by electrolysis according to claim 1, characterized in that: The pH of the electrolyte is 2.5-4.5, the electrolysis temperature is 55-65°C, and the current density is 30-40A / dm 2 .

8. The method for producing nickel foil by electrolysis according to claim 1, characterized in that: The distance between the anode and the cathode is 5 to 20 mm; Preferably, the distance between the two poles is 10-20 mm.

9. The method for producing nickel foil by electrolysis according to any one of claims 1 to 8, characterized in that: The electrolysis time is 10 to 60 seconds; Preferably, the electrolysis time is 20 to 30 seconds.

10. The method for producing nickel foil by electrolysis according to claim 1, characterized in that: The titanium plate after the electrodeposition is taken out from the electrolyte, and then washed and dried in sequence, and then the metal layer formed after the deposition is peeled off to obtain the nickel foil.

Citation Information

Patent Citations

  • Electroplating of low-stress nickel

    CN1213019A

  • Copper-alloy chemical nickeling process

    CN1896307A

  • Nickel electroplating electrolyte

    US3502550A